ANALISIS SEGMENTASI KOPI DI COFFEE SHOP BOJONEGORO - Widayanti, Sri; Hakim, Burhanul; Winarno, Sri Tjondro (Agridevina : Berkala Ilmiah Agribisnis, 2020)
This study aims to analyze the coffee market segmentation in the coffee shop based on demographic characteristics, consumer behavior and psychography. This research was conducted in a coffee shop in Bojonegoro named Damai Cafe using primary data and secondary data. The data collection method used is by interviewing consumers and related parties. The number of samples used was 50 respondents. The data analysis used was cluster analysis and crosstab. The results showed that Segment 1 is a consumer who likes to drink coffee. Meanwhile, segment 2 is a consumer who is more consumptive, but does not like coffee drinks. DOi :  https://doi.org/10.33005/adv.v9i2.2530